2017
DOI: 10.3390/ijms18030517
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Autism-Related Symptoms in Children with Prader-Willi Syndrome: A Case Study

Abstract: Prader-Willi syndrome (PWS), a rare genetic disorder caused by the lack of expression of paternal genes from chromosome 15q11-13, has been investigated for autism spectrum disorder (ASD) symptomatology in various studies. However, previous findings have been variable, and no studies investigating ASD symptomatology in PWS have exclusively studied children. We aimed to characterize social communication functioning and other ASD-related symptoms in children with PWS, and assessed agreement across measures and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Conversely, in childhood and adulthood, the patients display hyperphagia and poor satiety, which leads to early severe obesity with endocrine dysfunction (impaired sexual development and growth, central hypothyroidism) and intellectual disabilities. This syndrome is also associated with psychiatric manifestations, including symptoms that can be connected with several DSM and ICD diagnoses, such as intellectual disability, autism spectrum disorders 7 , schizophrenic disorders 8 , addictive behaviors 9 , 10 , obsessive-compulsive disorders 11 , attention deficit hyperactivity disorder (ADHD), and mood disorders 12 . Besides ID that is common, the heterogeneity in these potential ICD and DSM diagnoses indicates the limitations of these classifications, especially for comprehensive genetic models.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in childhood and adulthood, the patients display hyperphagia and poor satiety, which leads to early severe obesity with endocrine dysfunction (impaired sexual development and growth, central hypothyroidism) and intellectual disabilities. This syndrome is also associated with psychiatric manifestations, including symptoms that can be connected with several DSM and ICD diagnoses, such as intellectual disability, autism spectrum disorders 7 , schizophrenic disorders 8 , addictive behaviors 9 , 10 , obsessive-compulsive disorders 11 , attention deficit hyperactivity disorder (ADHD), and mood disorders 12 . Besides ID that is common, the heterogeneity in these potential ICD and DSM diagnoses indicates the limitations of these classifications, especially for comprehensive genetic models.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Bennett et al, tried to characterize ASD symptoms in children with PWS using Autism Diagnostic Observation Schedule‐2 (ADOS‐2), the Social Communication Questionnaire (SCQ), Social Responsiveness Scale‐2 (SRS‐2), Social Skills Improvement System‐Rating Scales (SSIS‐RS), and the Vineland Adaptive Behavioral Scales‐II (VABS‐II). They found discrepancy in parent‐reported measurements of ASD symptom severity and observation‐based diagnosis through ADOS‐2 (Bennett, Hodgetts, Mackenzie, Haqq, & Zwaigenbaum, ). As the ABC is a parent/caregiver reported measure, this may have influenced the accuracy of our scores in comparison to a validated provider based tool.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing SCQ, ADOS‐2 and clinical diagnosis of ASD in PWS found that SCQ and ADOS‐2 had high negative predictive values but also had high false positive rates leading to an overestimation of ASD diagnosis (Dykens et al, ). In addition, Bennet et al noted that none of the children who met ASD cut‐off with screening tools such as SCQ or ADOS met clinical best estimate criteria for ASD based on DSM‐5 because of inconsistencies among measures (Bennett et al, ). This may be why we had different rates of ASD in our PWS cohorts than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…PWS is characterized by hyperphagia, elevated ghrelin concentrations, and increased risk for obesity [93,94]. PWS is also associated with higher rates of social-communication impairments and repetitive behaviors [95], although the degree to which symptoms meet diagnostic criteria for ASD varies across studies, emphasizing that ASD symptom measures require careful consideration of developmental profile and overall clinical context [95,96]. That said, genetic mechanisms underlying the association between Prader Willi and ASD may underlie obesity risk related to hyperphagia in a subset of individuals with ASD [97].…”
Section: Geneticsmentioning
confidence: 99%